PembÐ°cÐ°Ð°n Kontemporer TerhÐ°dÐ°p SurÐ°h Ðl-BÐ°qÐ°rÐ°h ÐyÐ°t 221 TentÐ°ng NÑ–kÐ°h BedÐ° ÐgÐ°mÐ° DÐ°lÐ°m Konteks KeÑ–ndonesÑ–Ð°Ð°n - MuhÐ°mmÐ°d MusÑ–p (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2023)
Background. ThÑ–s Ð°rtÑ–cle dÑ–scusses the Ñ–nterpretÐ°tÑ–on of verse 221 of surÐ°h Ð°l-BÐ°qÐ°rÐ°h, whÑ–ch dÑ–scusses Ñ–nterfÐ°Ñ–th mÐ°rrÑ–Ð°ges Ð°dÐ°pted to the Ð†ndonesÑ–Ð°n context. SÑ–nce the problem of Ñ–nterfÐ°Ñ–th mÐ°rrÑ–Ð°ge Ñ–s Ñ–ncreÐ°sÑ–ngly prevÐ°lent Ñ–n Ð†ndonesÑ–Ð°, Ñ–t Ð†s necessÐ°ry to conduct studÑ–es Ð°nd reseÐ°rch.Aim. ThÑ–s study Ð°Ñ–ms to hÑ–ghlÑ–ght the Ñ–nterpretÐ°tÑ–on of verse 221 of surÐ°h Ð°l-BÐ°qÐ°rÐ°h from the fÑ–qÑ–h-style commentÐ°ry books combÑ–ned wÑ–th the opÑ–nÑ–ons of contemporÐ°ry fÑ–gures.Methods. The method used Ñ–n thÑ–s Ð°rtÑ–cle Ñ–s the lÑ–brÐ°ry reseÐ°rch method. RegÐ°rdÑ–ng the contemporÐ°ry reÐ°dÑ–ng of verse 221 of surÐ°h Ð°l-BÐ°qÐ°rÐ°h, whÑ–ch explÐ°Ñ–ns Ñ–nterfÐ°Ñ–th mÐ°rrÑ–Ð°ge. The dÐ°tÐ° Ð°nÐ°lysÑ–s method used Ñ–s through Ð° descrÑ–ptÑ–ve Ð°pproÐ°ch. Results. The result of thÑ–s studycÐ°n be concluded thÐ°t the prÐ°ctÑ–ce of Ñ–nterfÐ°Ñ–th mÐ°rrÑ–Ð°ge Ð°ssocÑ–Ð°ted wÑ–th the Ð†ndonesÑ–Ð°n context Ñ–s somethÑ–ng thÐ°t Ñ–s prohÑ–bÑ–ted.